(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The text of this article contains a study of the image of the ornament of its location and interpretation, in the costumes of the peoples of Surkhandarya. Also considered is the cut and form of clothing of the inhabitants of Surkhandarya, the formation of clothing for centuries under the influence of local living conditions, climate, occupation, as well as economic and cultural ties with neighboring peoples.